A Contribution to the Apprehension of Third-Wave Military Coups in Africa - (:unkn) unknown (My University, 2024)
The recent spreading upsurge of military coups in Africa is stirring up passionate activism and intellectual energies, as is the custom. From these numerous movements, a consistent pattern has emerged, which has even become a doxa: military coups are a source of destabilization and political instability in Africa. Against this backdrop, and without dismissing that pattern, this contribution first undertakes a taxonomy of the various military coups perpetrated across the African continent, as evidenced by the term “third-wave” in the title, and goes on to demonstrate that the new wave of military coups is likely to play a key role in Africa’s quest for self-reliance. Thus, through the lens of philosophy, history, law and related disciplines, this highly nuanced reflection argues that some of the military coups executed during the aforementioned wave should be considered as the “negation” from which could emerge the “negation of the negation”, corresponding in this case to a rejection of the institutional humiliation suffered by the State in Africa, and a genuine quest for its sovereignty.
Keywords: African Research